STRENGTHENING PANCASILA EDUCATION THROUGH TEACHER CAPACITY AND CONTEXTUAL CURRICULUM ENACTMENT IN A REMOTE SCHOOL - Kirie Natalia Seleky; Fatimah Sialana; Lisye Salamor (CV. TOTUS TUUS, 2026)
Improving Pancasila Education in geographically and infrastructurally constrained schools requires alignment between teacher capacity, curriculum interpretation, school leadership, and locally feasible resources. This article presents a secondary qualitative reanalysis of an archived single-school fieldwork record from SMP Negeri 02 Fena Fafan, South Buru, Indonesia. The archive contains dated observation summaries, interview excerpts from school leaders, teachers, and Grade VII-IX students, and references to school documents collected in July 2025; however, the exact participant total, raw recordings, full instruments, and systematic student-outcome measures were not available. A hybrid thematic synthesis combined inductive coding with sensitizing concepts drawn from curriculum-enactment, instructional-leadership, professional-learning, culturally relevant pedagogy, and civic-education scholarship. The archived evidence documents uneven subject-matter mastery, lecture and note-taking practices, limited contextual materials, incomplete Merdeka Curriculum understanding, and restricted digital access. It also documents enabling practices, including supervision, peer knowledge sharing, selective use of Buru language, parent-school communication, discussion, group work, video, and shared-device learning. The analysis proposes, rather than tests, a framework in which principal-led curriculum co-design links professional capacity to contextual enactment, while local-language scaffolding and low-bandwidth pedagogy operate as context-specific enabling conditions. The study offers analytically transferable propositions for similar remote-school contexts, but no causal or statistical generalization is claimed. Future multisite research should verify the framework with complete sampling, ethics, instrument, and student-outcome documentation.